From Websites to Wal-Mart: Youth, Identity Work, and the Queering of Boundary Publics in Small Town, USA - Gray, Mary L. (American Studies, 2007)
Drawing from a larger ethnographic project, this paper discusses rural young people's construction of “boundary publics” as a strategy for space making and locations for what I describe as queer identity work. Building off of the rich literature theorizing both the public sphere and responsive counterpublics, the notion of a boundary public is offered to better address the infrastructural constraints of rural communities and as a critical site to explore young people’s experiences crafting queer sexual and gender identities. Contrary to the presumed invisibility of queer genders and sexualities in rural spaces, I argue that youth assert their presence in fabulously conspicuous ways. Youth pieced together resources in and beyond their communities, carving out what I call “boundary publics”—from personal and organizational websites created by and for other rural queer young people to drag outings at the local Wal-Mart and a local church’s SkatePark. This paper provides a rich account of what rural queer youth do with and in the spaces around them. Their social interactions challenge the expectation that rural queer publics are unsustainable or poor imitations when compared to an urban queer scene. Arguing that late modern identities call for publics, this paper analyzes how rural queer and questioning youth craft such spaces in ways and locations one might not likely expect. Rather than counter or rebuff the mainstream or rural public sphere, the boundary publics of rural young people necessarily move among both the centers and margins of their rural communities. These occupations are activities of what I describe as queer identity work. Youth crisscross the commercial zones of chain stores and the nonprofit corporate structures of non-governmental LGBT advocacy organizations. They also occupy and work the spaces of public parks and meeting halls of organized religions. Rural queer young people absorb, recycle, and recuperate these spaces to make them their own—if only temporarily so. And, in increasingly complicated ways, these youth take up what I shall call new mediascapes such as personal and group websites and listservs. Each of these types of occupation or moments of queer identity work can be understood as liberating and impermanent. Indeed, it is the fragility of these competing qualities that make boundary publics such productive locations of rural queer youth identity work.The fragility of boundary publics also illustrates the elemental entanglements between these publics and the broader public sphere.The examples of queer rural youth boundary publics argue against theorizing that new media can produce independent publics insolated or removed from their offline contexts. In highlighting the constitutive matrices of boundary publics and public spheres, rural queer young people’s experiences of public-ness brings into question divisions of public and private spaces more broadly.